Las Cruces, poblado próximo - Rosal, Rafael; Figueroa, Ray; Buonafina, Giacomo (Casa Comal, 2006)
Set in Aldea Las Cruces, a small mountain community in the highlands of Guatemala, in 1986, towards the end of that country's civil unrest. Tells the story of a small band of guerrillas who decide to defend the community from extermination, even though they are outnumbered by the forces of the country's military junta.